CSIG-07. TARGETING CELL POLARITY PROTEINS FROM THE SCRIBBLE COMPLEX DISRUPTS GLIOBLASTOMA STEM CELL VIABILITY AND INVASION IN NEURAL TISSUE. (11th November 2019) - Kundu, Somanath; Nandhu, Mohan; Longo, Sharon; Longo, John; Richardson, Timothy; Chin, Lawrence; Viapiano, Mariano
Abstract: Despite their molecular heterogeneity, glioblastomas (GBMs) retain a common phenotypical feature, which is their diffuse invasion through neural tissue that makes complete resection impossible. This invasive ability requires changes in cell polarity for the tumor cells to migrate following cues from their microenvironment. Cytoskeleton-associated proteins of the DLG family are part of the Scribble polarity complex that maintains stable cell-cell junctions; accordingly, these proteins are "tumor suppressors" usually downregulated in solid tumors. However, we have found that one family member, DLG5, is highly upregulated in GBM compared to other solid tumors. Results from Western blot, immunohistochemistry, and RNAseq confirmed that DLG5 is highly expressed in GBM compared to normal brain and is the predominant DLG family member in GBM stem cells (GSCs). DLG5 knockdown reduced cell viability after four days in culture, but had an immediate (24h) negative effect on cell invasion through Matrigel and brain tissue. At the molecular level DLG5 knockdown downregulated components of the Sonic-Hedgehog pathway, including PTCH1 and Gli1, as well as SHH-regulated downstream genes (CCND2, cMYC and CD44). Accordingly, DLG5-deficient GSCs showed reduced Gli1 phosphorylation in response to exogenous SHH and lacked increased invasiveness in presence of SHH compared to control GSCs. Ongoing experiments are evaluating the growth and invasion of DLG5-deficient GSCs in response to signals derived from oligodendrocyte progenitor cells, which are a major source of SHH in the postnatal brain. Taken together, our results describe for the first time the expression of DLG proteins in malignant gliomas and reveal an unexpected pro-tumoral function for the protein DLG5 that differs from its proposed tumor-suppressor role in other solid cancers. Targeting DLG5 could disrupt the ability of GSCs to respond to signals enriched in the neural microenvironment (SHH), contributing to the long-term control of residual tumor after surgical resection.